Functional characterization and differential expression studies of squalene synthase from Withania somnifera - Gupta, Neha; Sharma, Poonam; Kumar, R. J. Santosh; Vishwakarma, Rishi K.; Khan, Bashir Mohammad (Molecular Biology Reports, 2012)
Squalene synthase (SQS: EC 2.5.1.21) is a potential branch point regulatory enzyme and represents the first committed step to diverge the carbon flux from the main isoprenoid pathway towards sterol biosynthesis. In the present study, cloning and characterization of Withania somnifera squalene synthase (WsSQS) cDNA was investigated subsequently followed by its heterologous expression and preliminary enzyme activity. Two different types of WsSQS cDNA clones (WsSQS1and WsSQS2) were identified that contained an open reading frames of 1,236 and 1,242 bp encoding polypeptides of 412 and 414 amino acids respectively. Both WsSQS isoforms share 99 % similarity and identity with each other. WsSQS deduced amino acids sequences, when compared with SQS of other plant species, showed maximum similarity and identity with Capsicum annuum followed by Solanum tuberosum and Nicotiana tabacum. To obtain soluble recombinant enzymes, 24 hydrophobic amino acids were deleted from the carboxy terminus and expressed as 6X His-Tag fusion protein in Escherichia coli. Approximately 43 kDa recombinant protein was purified using Ni-NTA affinity chromatography and checked on SDS-PAGE. Preliminary activity of the purified enzymes was determined and the products were analyzed by gas chromatograph-mass spectrometer (GC-MS). Quantitative real-time PCR (qRT-PCR) analysis showed that WsSQS expresses more in young leaves than mature leaves, stem and root.
Keywords: Gas chromatograph-Mass Spectrometer (GC-MS); qRT-PCR; Squalene synthase; Withania somnifera

Functional characterization of a flavonoid glycosyltransferase gene from withania somnifera (Ashwagandha) - Singh, Somesh; Vishwakarma, Rishi. K.; Kumar, R. J. Santosh; Sonawane, Prashant D.; Ruby; Khan, Bashir Mohammad (Applied Biochemistry and Biotechnology, 2013)
Glycosylation of flavonoids is mediated by family 1 uridine diphosphate (UDP)-dependent glycosyltransferases (UGTs). Until date, there are few reports on functionally characterized flavonoid glycosyltransferases from Withania somnifera. In this study, we cloned the glycosyltransferase gene from W. somnifera (UGT73A16) showing 85-92 % homology with UGTs from other plants. UGT73A16 was expressed as a His(6)-tagged fusion protein in Escherichia coli. Several compounds, including flavonoids, were screened as potential substrates for UGT73A16. HPLC analysis and hypsochromic shift indicated that UGT73A16 transfers a glucose molecule to several different flavonoids. Based on kinetic parameters, UGT73A16 shows more catalytic efficiency towards naringenin. Here, we explored UGT73A16 of W. somnifera as whole cell catalyst in E. coli. We used flavonoids (genistein, apigenin, kaempferol, naringenin, biochanin A, and daidzein) as substrates for this study. More than 95 % of the glucoside products were released into the medium, facilitating their isolation. Glycosylation of substrates occurred on the 7- and 3-hydroxyl group of the aglycone. UGT73A16 also displayed regiospecific glucosyl transfer activity towards 3-hydroxy flavone compound, which is the backbone of all flavonols and also for a chemically synthesized compound, not found naturally. The present study generates essential knowledge and molecular as well as biochemical tools that allow the verification of UGT73A16 in glycosylation.
Keywords: Flavonoid; glycosylation; Glycosyltransferase; Hypsochromic shift; Plant secondary product glycosyltransferase (PSPG); Withania somnifera

Functional characterization of a glucosyltransferase specific to flavonoid 7-O-glucosides from withania somnifera - Kumar, R. J. Santosh; Ruby; Singh, Somesh; Sonawane, Prashant D.; Vishwakarma, R. K.; Khan, Bashir Mohammad (Plant Molecular Biology Reporter, 2013)
Flavonoids are a large class of phenylpropanoid-derived secondary metabolites, which are usually glycosylated by UDP-glycosyltransferases with one or more sugar groups. Here, we report the cloning and biochemical characterization of a flavonoid glycosyltransferase gene from Withania somnifera (WsGT), which is an important medicinal plant used in Ayurvedic formulations. Using PCR primers, designed for a highly conserved region of previously reported glycosyltransferases, we were able to isolate the corresponding fragment of the WsGT gene. Rapid amplification of cDNA ends (RACE) was then employed to isolate full-length cDNA, which had an open reading frame of 1,371 bp that encode for 456 amino acids. Phylogenetic analysis indicated that WsGT was similar to that of family 1 GT-B glycosyltransferase. Biochemical analysis revealed that WsGT interacts with UDP-glucose and was capable of regiospecifically glycosylating flavonoid-7-ols, such as apigenin, naringenin, luteolin, diadzein and genistein. Expression profiling studies showed that WsGT was highly expressed in young and mature leaves of W. somnifera. Furthermore, exposure to salicylic acid enhanced the expression of WsGT in the leaves and heat shock treatment resulted in decreased expression of WsGT after an initial increase. This may suggest the role of WsGT in response to abiotic/biotic stresses.
Keywords: Diadzein; Flavonoids; Glycosyltransferase; Withania somnifera

Molecular cloning, biochemical characterization, and differential expression of an acetyl-CoA C-acetyltransferase gene (AACT) of brahmi (Bacopa monniera) - Vishwakarma, Rishi K.; Ruby; Singh, Somesh; Sonawane, Prashant D.; Srivastava, Sameer; Kumari, Uma; Kumar, R. J. Santosh; Khan, Bashir Mohammad (Plant Molecular Biology Reporter, 2013)
Bacopa monniera (Brahmi) is an important Indian medicinal herb found in wet damp and marshy places. It produces medicinally important compounds known as bacosides along with alkaloids like brahmine and herpestine. Bacosides are triterpenoid saponins and their biosynthesis takes place via the isoprenoid pathway starting with acetyl-CoA. Acetyl-CoA C-acetyltransferase (AACT; EC 2.3.1.9), also known as acetoacetyl-CoA thiolase (Thiolase II), catalyzes the condensation of two acetyl-CoA to form 4-C compound acetoacetyl-CoA. Acetoacetyl-CoA is an important starting molecule for biosynthesis of various metabolites. Here, we report the cDNA cloning and characterization of acetyl-CoA C-acetyltransferase gene from B. monniera. The full-length gene was isolated using a RACE PCR protocol. The cDNA encoding AACT was designated as BmAACT (FJ947159) revealed an ORF of 1,218 bp and 405 amino acids, and shares 80 % similarity with other plant AACTs. Phylogenetic analysis showed that BmAACT is related closely to other dicot plants AACTs. The BmAACT gene was over-expressed in Escherichia coli as a 6X His-tag fusion protein and purified to homogeneity by Ni-NTA and gel filtration chromatography. Activity of recombinant protein was confirmed by thiolytic cleavage of acetoacetyl-CoA in the presence of 5 mM Mg2+, showing K (m) and V (max) of 20.67 mu M and 96.21 mu mol/min, respectively, with high catalytic efficiency (k (cat) = 2.30 x 10(5) min(-1)). Quantitative real-time PCR analysis showed that the expression of BmAACT is tissue-specific, and accumulation of transcripts is greater in roots and petals, followed by sepals, stem, leaf and pedicel.
Keywords: Acetyl-CoA C-acetyltransferase; Bacopa monniera; Isoprenoid pathway; Triterpenoid saponin

Molecular cloning and characterization of genistein 4'-O-glucoside specific glycosyltransferase from Bacopa monniera - Ruby; Kumar, R. J. Santosh; Vishwakarma, Rishi K.; Singh, Somesh; Khan, Bashir Mohammad (Molecular Biology Reports, 2014)
Health related benefits of isoflavones such as genistein are well known. Glycosylation of genistein yields different glycosides like genistein 7-O-glycoside (genistin) and genistein 4'-O-glycoside (sophoricoside). This is the first report on isolation, cloning and functional characterization of a glycosyltransferase specific for genistein 4'-O-glucoside from Bacopa monniera, an important Indian medicinal herb. The glycosyltransferase from B. monniera (UGT74W1) showed 49 % identity at amino acid level with the glycosyltransferases from Lycium barbarum. The UGT74W1 sequence contained all the conserved motifs present in plant glycosyltransferases. UGT74W1 was cloned in pET-30b (+) expression vector and transformed into E. coli. The molecular mass of over expressed protein was found to be around 52 kDa. Functional characterization of the enzyme was performed using different substrates. Product analysis was done using LC-MS and HPLC, which confirmed its specificity for genistein 4'-O-glucoside. Immuno-localization studies of the UGT74W1 showed its localization in the vascular bundle. Spatio-temporal expression studies under normal and stressed conditions were also performed. The control B. monniera plant showed maximum expression of UGT74W1 in leaves followed by roots and stem. Salicylic acid treatment causes almost tenfold increase in UGT74W1 expression in roots, while leaves and stem showed decrease in expression. Since salicylic acid is generated at the time of injury or wound caused by pathogens, this increase in UGT74W1 expression under salicylic acid stress might point towards its role in defense mechanism.
Keywords: Bacopa monniera; Expression analysis; Glycosyltransferase; Immuno-localization; Plant secondary product glycosyltransferase motif

Rapid efficient synthesis and characterization of silver, gold, and bimetallic nanoparticles from the medicinal plant plumbago zeylanica and their application in biofilm control - Salunke, Gayatri R.; Ghosh, Sougata; Kumar, R. J. Santosh; Khade, Samiksha; Vashisth, Priya; Kale, Trupti S.; Chopade, Snehal; Pruthi, Vikas; Kundu, Gopal; Bellare, Jayesh R.; Chopade, Balu Ananda (International Journal of Nanomedicine, 2014)
Background: Nanoparticles (NPs) have gained significance in medical fields due to their high surface-area-to-volume ratio. In this study, we synthesized NPs from a medicinally important plant - Plumbago zeylanica. Materials and methods: Aqueous root extract of P. zeylanica (PZRE) was analyzed for the presence of flavonoids, sugars, and organic acids using high-performance thin-layer chromatography (HPTLC), gas chromatography-time of flight-mass spectrometry (GC-TOF-MS), and biochemical methods. The silver NPs (AgNPs), gold NPs (AuNPs), and bimetallic NPs (AgAuNPs) were synthesized from root extract and characterized using ultraviolet-visible spectra, X-ray diffraction (XRD), energy-dispersive spectrometry (EDS), transmission electron microscopy (TEM), and dynamic light scattering (DLS). The effects of these NPs on Acinetobacter baumannii, Staphylococcus aureus, and Escherichia coli biofilms were studied using quantitative biofilm inhibition and disruption assays, as well as using fluorescence, scanning electron microscopy, and atomic force microscopy. Results: PZRE showed the presence of phenolics, such as plumbagin, and flavonoids, in addition to citric acid, sucrose, glucose, fructose, and starch, using HPTLC, GC-TOF-MS, and quantitative analysis. Bioreduction of silver nitrate (AgNO3) and chloroauric acid (HAuCl4) were confirmed at absorbances of 440 nm (AgNPs), 570 nm (AuNPs), and 540 nm (AgAuNPs), respectively. The maximum rate of synthesis at 50 degrees C was achieved with 5 mM AgNO3 within 4.5 hours for AgNPs; and with 0.7 mM HAuCl4 within 5 hours for AuNPs. The synthesis of AgAuNPs, which completed within 90 minutes with 0.7 mM AgNO3 and HAuCl4, was found to be the fastest. Fourier-transform infrared spectroscopy confirmed bioreduction, while EDS and XRD patterns confirmed purity and the crystalline nature of the NPs, respectively. TEM micrographs and DLS showed about 60 nm monodispersed Ag nanospheres, 20-30 nm Au nanospheres adhering to form Au nanotriangles, and about 90 nm hexagonal blunt-ended AgAuNPs. These NPs also showed antimicrobial and antibiofilm activity against E. coli, A. baumannii, S. aureus, and a mixed culture of A. baumannii and S. aureus. AgNPs inhibited biofilm in the range of 96%-99% and AgAuNPs from 93% to 98% in single-culture biofilms. AuNPs also showed biofilm inhibition, with the highest of 98% in S. aureus. AgNPs also showed good biofilm disruption, with the highest of 88% in A. baumannii. Conclusion: This is the first report on rapid and efficient synthesis of AgNPs, AuNPs and AgAuNPs from P. zeylanica and their effect on quantitative inhibition and disruption of bacterial biofilms.
Keywords: AgAuNPs; AgNPs; AuNPs; biofilm inhibition and disruption; GC-TOF-MS; P. zeylanica